UZBEKISTAN PARA SPORTS MOVEMENT HISTORY AND STAGES OF DEVELOPMENT (Web of Teachers: Inderscience Research, 2026)
This article comprehensively studies the role of people with disabilities in Paralympic competitions and the historical development of the para sports movement in Uzbekistan from 1991 to the present. The study analyzes the global history of the Paralympic movement, the dynamics of Uzbekistan's participation in international competitions, the socio-psychological role of athletes with disabilities, and the evolution of state policy in this area. Based on regulatory legal documents, reports of the International Paralympic Committee, and scientific literature, three historical stages of Uzbek para sports are distinguished. The article shows that athletes with disabilities are not only participants in Paralympic competitions who demonstrate sports results, but also are active catalysts for social change in society.